Profiling agricultural engineering technologies for mechanizing smallholder agriculture in Uganda - Wanyama, J.; Banadda, N.; Kiyimba, F.; Okurut, S.; Zziwa, A.; Kabenge, I.; Mutumba, C.; Tumutegyereize, P.; Komakech, A. J.; Kiggundu, N. (Agricultural Engineering International: CIGR Journal, 2016)
Developing countries are grappling with numerous challenges including feeding rapidly growing populations, alleviating poverty, protecting the environment, and mitigating adverse impacts of climate change. For the coming years, one of the main agricultural development agenda for Sub-Saharan Africa (SSA) should be to increase agricultural productivity and production to achieve food security through agricultural mechanization with Agricultural Engineering Technologies (AETs) as major inputs. However, there is paucity of information on the status of existing AETs and their contribution to mechanizing smallholder agriculture which is crucial to effective planning and strategy formulation. Therefore, the overarching objective of this paper is to review the past and present status, the constraints to adoption and future of AETs in Uganda in the context of mechanizing smallholder agriculture. Several proven AETs developed through research institutions and universities have been profiled in different areas of farm power and mechanization systems, agro-processing for value addition; renewable energy systems; and water harnessing and utilization. Availability and prudent use of these AETs along the value chain has the potential to enhance labor use and efficiency, provide greater precision and timeliness in farm operations, reduce postharvest loses, contributing to adding value to products and profitability of farming through proper handling, drying, cleaning, grading, processing, preservation, packaging and storage. The future of AETs in Uganda is hinged on addressing the aspects on appropriateness of the AETs in the smallholder agriculture context and standardizing of AET. Furthermore, human resource capacity development through enhancement of technical skills in AE, increased private sector engagement, economic incentives and innovation protection should be an integral part of the future strategies for development and increased adoption of AETs.
Keywords: Agricultural engineering; Mechanization; Smallholder farmers; Food security